Influence of assembly stress on ultimate load carrying capacity of transmission towers. Issue 1 (1st November 2022) - Yu, Xinmin; Lin, Ruizong; Li, Songbo; Bai, Junfeng; Kong, Yong
Abstract : In recent years, for the influence of all kinds of natural disasters, the transmission tower's collapsing or line's damage presents a growing trend. The influence of assembly stress in transmission towers is often ignored when people analyze the accidents. To study the actual influence of assembly stress, the production process of assembly stress should be summarized and simulated. Find out the method to calculate and simulate assembly stress by using the finite element analysis software. Trussed beam hybrid finite element model is built. The ultimate load carrying capacity with the influence of assembly stress is studied. The position which is unfavorable for dimension error is determined through the variation of bar quantity and the position of dimension error. It founds that influence of assembly stress is small when there is only one pole existing size error in the transmission towers and the size error should small than 1% of the pole's length; When there are a number of poles which are located at the tower leg existing size error will produce great influence on the Ultimate load carrying capacity of the transmission towers.